Persepsi Anggota Kelompok Pembudidaya Ikan Tentang Kapasitas Penyuluh Perikanan Di Provinsi Sumatra Barat - Metalisa, Rindi; Indah; Nugroho, Firman (Fakultas Pertanian Universitas Jember, 2025)
Fisheries extension is a learning process for capacity building. This study aims to analyze the perseption of fish farmer group members about the capacity of fisheries extension workers in West Sumatra Province. The method used was survey method. The number of respondents used as the object of this research was 34 people, which was considered sufficient to obtain research data on the persepsi of fish farmer group members about the capacity of extension workers. The types of data collected include primary data and secondary data. This data was obtained from direct interviews using questionnaires, observation and documentation. The results of the research are: The perseption of fish farmer group members on the capacity of fisheries extension workers is well done in the process of disseminating extension material, applying extension methods, developing institutions, evaluating the implementation of extension, making potential data and making reports on the implementation of extension. In the process of training conducted by extension to cultivation in the form of determining quality fish seeds and broodstock, measuring water quality, preventing the threat of fish diseases so that the business developed in fish farming can be managed properly.